Legal Implication of the Tradition Regarding Prophet’s Abstenance from the Reconstruction of Ka‘bah - Fahd bin saleh al-Ajlan (الدراسات الإسلامية, 2017)
This paper examines the tradition reported by ‘Aishah (RA), the mother of the faithful, regarding the Prophet’s preference of avoiding reconstruction of Ka‘bah on the original plan of Prophet Ibrahim (AS). The writer provides necessary details of this report and proceeds to examine the legal implications of this tradition. He cites the relevant views of the early and later jurists and concludes that the principle of taking into consideration the possible misperceptions among people, as inferred from this tradition, is not applicable without limits. Rather, the writer asserts, this principle has been qualified by a number of conditions identified in the injunctions of the Shari‘ah. The foremost condition is that this principle could only be applied in the category of mustahabbat (acts recommended by the Shari‘ah) but never in the category of wajibat (obligatory acts). Even in the former category, its application is subject to many conditions, as the writer elaborates.